Investigating Biochemical and Developmental Dependencies of Lignification with a Click-Compatible Monolignol Analog in Arabidopsis thaliana Stems - Pandey, Jyotsna L.; Kiemle, Sarah N.; Richard, Tom L.; Zhu, Yimin; Cosgrove, Daniel J.; Anderson, Charles T. (Frontiers in Plant Science, 2016)
Lignin is a key structural component of plant cell walls that provides rigidity, strength, and resistance against microbial attacks. This hydrophobic polymer also serves a crucial role in water transport. Despite its abundance and essential functions, several aspects of lignin biosynthesis and deposition remain cryptic. Lignin precursors are known to be synthesized in the cytoplasm by complex biosynthetic pathways, after which they are transported to the apoplastic space, where they are polymerized via free radical coupling reactions into polymeric lignin. However, the lignin deposition process and the factors controlling it are unclear. In this study, the biochemical and developmental dependencies of lignification were investigated using a click-compatible monolignol analog, 3-O-propargylcaffeyl alcohol (3-OPC), which can incorporate into both in vitro polymerized lignin and Arabidopsis thaliana tissues. Fluorescence labeling of 3-OPC using click chemistry followed by confocal fluorescence microscopy enabled the detection and imaging of 3-OPC incorporation patterns. These patterns were consistent with endogenous lignification observed in different developmental stages of Arabidopsis stems. However, the concentration of supplied monolignols influenced where lignification occurred at the subcellular level, with low concentrations being deposited in cell corners and middle lamellae and high concentrations also being deposited in secondary walls. Experimental inhibition of multiple lignification factors confirmed that 3-OPC incorporation proceeds via a free radical coupling mechanism involving peroxidases/laccases and reactive oxygen species (ROS). Finally, the presence of peroxide-producing enzymes determined which cell walls lignified: adding exogenous peroxide and peroxidase caused cells that do not naturally lignify in Arabidopsis stems to lignify. In summary, 3-OPC accurately mimics natural lignification patterns in different developmental stages of Arabidopsis stems and allows for the dissection of key biochemical and enzymatic factors controlling lignification.